Effectiveness of Blended Learning Model-Based on “Kutub Al-Tis’ah” Application in Improving Students’ Critical Thinking in Hadith Study Courses - Channa, Lilik (Didaktika Religia, 2022)
This study aims to analyze the differences in students’ critical thinking skills improvement between students that joined the Blended Learning model based on the Kutub al-Tis’ah and students who get the ordinary learning model. This study uses a quasi-experimental method with purposive sampling. The research samples were two classes from the Architecture Study Program of the State Islamic University of Sunan Ampel Surabaya in 2020/2021. Experiment class was a class with Blended Learning model based on the Kutub al-Tis’ah whether the conventional class was control class. The Blended model is effective if the post-test score of the Experiment class is better than the Control class. The results of the study showed that the average post-test value for the Experiment class was 90,32 with a variance of 6,799 and the Conventional class had an average value of 65,81 with a variance of 5,872. The hypothesis test of the similarity of the two post-test data averages was carried out through a normality test whose calculation results using Kolmogorov-Smirnov and Spiro-Wilk showed the post-test values for both the Experimental class and Control class were normally distributed with Sig 0,200 > =0,05. While the homogeneity test of the calculation results using the Levene test showed that the post-test value of both the Experiment class and the Control class was homogeneous with Sig 0,206 > = 0,05. While the statistical test calculation results obtained a value of Sig 0.00 < = 0.05, which means rejecting H0. The average post-test value for the Experiment class is greater than the average post-test value for the Control class that means the blended learning model based on the Kutub al-Tis’ah application is effective for improving students’ critical thinking for Hadith Studies courses.